Heterogeneous Gold Nanoparticle-Based Catalysts for the Synthesis of Click-Derived Triazoles via the Azide-Alkyne Cycloaddition Reaction - Librando, Ivy L. (2021)
A supported gold nanoparticle-catalyzed strategy has been utilized to promote a click chemistry reaction for the synthesis of 1,2,3-triazoles via the azide-alkyne cycloaddition (AAC) reaction. While the advent of effective non-copper catalysts (i.e., Ru, Ag, Ir) has demonstrated the catalysis of the AAC reaction, additional robust catalytic systems complementary to the copper catalyzed AAC remain in high demand. Herein, Au nanoparticles supported on Al2O3, Fe2O3, TiO2 and ZnO, along with gold reference catalysts (gold on carbon and gold on titania supplied by theWorld Gold Council) were used as catalysts for the AAC reaction. The supported Au nanoparticles with metal loadings of 0.7–1.6% (w/w relative to support) were able to selectively obtain 1,4-disubstituted-1,2,3-triazoles in moderate yields up to 79% after 15 min, under microwave irradiation at 150 C using a 0.5–1.0 mol% catalyst loading through a one-pot three-component (terminal alkyne, organohalide and sodium azide) procedure according to the “click” rules. Among the supported Au catalysts, Au/TiO2 gave the best results.